县级政府在经济转型中的作用 = The role of county government in China's economy transformation - 姜德果 Jiang, De Guo (2008)
The major content of the thesis includes discussion of the theoretical basis of market economy and the methodology; summary of theoretical origin of the government intervention; analysis of the role county government plays in the economic transition. The main achievement of this paper is: suggestion that the macroeconomic policies adopted by the central government be effectively observed; proposal regarding the cultivation of the market where the notion of fairness and just is fully respected; advice on provision of information service and public goods; advocacy of proper definition of property right to protect the rights of enterprises; recommendation of the sustainable development of countywide economy. On this basis, real cases are carefully studied to test the importance of county government's intervention during the process of economic transition.